2016
DOI: 10.1177/1524838016631129
|View full text |Cite
|
Sign up to set email alerts
|

Campus Sexual Assault: A Systematic Review of Prevalence Research From 2000 to 2015

Abstract: Sexual assault is a pervasive problem on university and college campuses in the United States that has garnered growing national attention, particularly in the past year. This is the first study to systematically review and synthesize prevalence findings from studies on campus sexual assault (CSA) published since 2000 ( n = 34). The range of prevalence findings for specific forms of sexual victimization on college campuses (i.e., forcible rape, unwanted sexual contact, incapacitated rape, sexual coercion, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
436
3
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 605 publications
(465 citation statements)
references
References 54 publications
22
436
3
4
Order By: Relevance
“…Relatedly, the measures of trust and perceptions of mandatory reporting were developed for this study, and were focused on (a) institutional responses to women sexual assault survivors and (b) aspects of RAs job roles related to mandatory reporting. College women are significantly more likely to experience sexual assault and their responses to assault may differ from college men's responses (e.g., Banyard et al., ; Fedina et al., ), and, as discussed in the introduction, RAs are a useful group in which to study mandatory reporting. Thus, the current study took a step toward the examination of an important and understudied topic, but future research will be needed to advance this work.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, the measures of trust and perceptions of mandatory reporting were developed for this study, and were focused on (a) institutional responses to women sexual assault survivors and (b) aspects of RAs job roles related to mandatory reporting. College women are significantly more likely to experience sexual assault and their responses to assault may differ from college men's responses (e.g., Banyard et al., ; Fedina et al., ), and, as discussed in the introduction, RAs are a useful group in which to study mandatory reporting. Thus, the current study took a step toward the examination of an important and understudied topic, but future research will be needed to advance this work.…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 20 to 50% of female college students are affected by IPV during their time in college (Fedina, Holmes, & Backes, 2018;Krebs et al, 2016;Nabors, 2010). Women in college are three times more likely to experience SV than their noncollege peers (Fisher et al, 2000).…”
Section: Violence Experiences In College Womenmentioning
confidence: 99%
“…Young women on college campuses are particularly vulnerable to experiencing intimate partner violence (IPV) and sexual violence (SV) (Aronowitz, ; Fisher, Cullen, & Turner, ; Krebs, Lindquist, Berzofsky, Shook‐Sa, & Peterson, ; Sinozich & Langton, ). An estimated 20 to 50% of female college students are affected by IPV during their time in college (Fedina, Holmes, & Backes, ; Krebs et al, ; Nabors, ). Women in college are three times more likely to experience SV than their noncollege peers (Fisher et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent large-scale surveys and systematic reviews of sexual coercion victimization among undergraduates have found prevalence rates ranging from 13% to 30% for women and 5% to 31% for men (Cantor et al, 2015;Fedina, Holmes, & Backes, 2018). Given the prevalence of victimization among college students, it is especially important to understand the relevance of oft-cited risk factors in this population, including psychopathic personality traits and beliefs and feelings about sex itself.…”
Section: Gender Perpetration Psychopathy Sexual Coercionmentioning
confidence: 99%